فعالية استخدام وسائل التعليم Flashcard لترقية المفردات لدى طلاب بالمدرسة الثانوية جاء الحق بنجكولو - Muhammad Zikri; Titin Anggraini; Nur Hidayat (UIN Fatmawati Sukarno Bengkulu, 2022)
The school of Ja al-Haq Bengkulu – it turned out that the students' mastery of language vocabulary has increased significantly than before. This increase in students' vocabulary proficiency appears as students are able to memorize the given vocabulary, use the vocabulary to form a sentence, and be able to translate into Arabic text. From this research is to determine the effectiveness of using Flashcard teaching aids to upgrade the vocabulary of seventh grade students in Islamic Junior Hight school Ja al-Haq Bengkulu.This study uses quantitative research using a quasi-experimental approach, and the data collection methods in this study are testing and documentation. The data sources in this study were seventh-grade students at the Islamic Junior Hight school Ja al-Haq Bengkulu. The data analysis technique in this research uses the normality test, homogeneity test, and t test.The results of the study showed, based on the research that was conducted, that there is no effect using Flashcard methods on the vocabulary results of students in the seventh grade at school. It came right.Keyword: Ja al-Haq, Flashcard, Vocabulary